IN VITRO DETERMINATION OF ANTI-OXIDANT AND ANTI-BACTERIAL ACTIVITIES OF VITEX NEGUNDO LINN. - MURALI KRISHNA. T; MEENA. G; KAVYA. T; SOMESHWAR. C; SOUMYA. J ASWAQ AHMED; RAJENDER. VADLURI; RAJESH GOUD. GAJULA (International Journal of Pharma and Bio Sciences, 2013)
The investigations were carried out to evaluate anti-oxidant and anti-bacterial activities, of stem methanol extract of vitex negundo at various concentrations. The methanol stem extract noticed significant scavenging activity on DPPH, superoxide, nitric oxide and hydrogen peroxide. The anti-bacterial activity was determined by agar diffusion well method using Bacillus subtilis, Staphylococcus aureus, Escherichia coli and Salmonella paratyphi. The methanol stem extract exhibited significant inhibitory effect on all tested organisms. The highest susceptibility was noticed with bacillus subtilis. The phytochemical analysis revealed the presence of various phytochemicals viz., alkaloids, saponins, cardic glycosides etc., which play a vital role as anti-microbial agents.